Pengembangan Kemampuan Menulis Cerita Pendek Berdasarkan Buku Bacaan Di MTSN 2 Indragiri Hilir - Aaliyah Vernanda; Dicky Orlando Sinaga; Dimas Prayoga; Hervita Yunani Harahap; Martua Silaban; Ramdhoni Kurnia Sandi; Risfal Fadhillah; Salma Chantika Nabilah; Syaniza Fatih; Yola Afrillya (Unri Conference Series: Community Engagement, 2025)
This community service activity aimed to enhance students’ ability to write short stories through a reading-based approach at MTsN 2 Indragiri Hilir. The training was conducted on July 22, 2025, involving 17 students selected as class representatives to participate as literacy ambassadors. The method combined interactive teaching and practical exercises, beginning with a theoretical session on the concepts and techniques of short story writing, followed by practice using reading materials as sources of inspiration. After the presentation, participants were given three days to develop their story outlines, which were then evaluated based on intrinsic elements, creativity, plot coherence, and language use. The results indicated an improvement in students’ skills in transforming ideas from reading into well-structured and creative short stories. Six best works were selected as recognition and motivation for continued literacy development. This activity demonstrates that a reading-based writing approach is effective in fostering creative literacy, enriching vocabulary, and building students’ confidence.